Introduction to the paradigm of concrete love - Rodas V., Nikolai (2011)
This article introduces an approach about de couple that was originally developed by Rodas (2011). It is talk about we need a whole vision in order we could study and change the love in our society. The paradigm is defined since its factors: ideology, philosophy, science and policy. Moreover, the text show how we can apply these factors (and the dimensions that are included) in the relationship of couple.